Assessment of a floating platform for testing a crossflow tidal turbine (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Field testing of tidal stream turbines is required to advance the technology readiness of emerging designs. Subsystem testing in the relevant field environment is vital at low cost to allow data acquisition whilst also making best use of the available resource. Floating platforms enable easy access for turbine testing when super-structure is not of interest, access to the upper water column ensure turbines are in the high flow region. This study considers the performance of a 20m by 4m barge and its mooring configuration during the operational testing of a crossflow turbine. The platform was deployed at the QML tidal test site in Strangford Narrows, Northern Ireland in Autumn 2024. The platform was designed using standard barges available locally and arranged for a single point mooring to hosts a 15kW rated turbine by developer Ocean Renewable Power Company (ORPC). The self-sufficient setup facilitated advanced rotor testing up to the rated power of the device in real-tidal flow conditions for a period of circa 8-weeks.The suitability of the platform and its mooring configuration is characterised by its response in six degrees of freedom. The yaw response is of particular interest for the single-point mooring facilitating passive alignment to the principal flow axes for flood and ebb but also a source of flow misalignment if unsteady. Initial assessment shows the platform to have good yaw response to off-axis flow with nominal 15° spread respective to principal flow direction. Platform motions were formally measured using a differential Global Positioning System (dGPS) and synchronised data recorded with electrical output from the turbine and the global thrust measured from load cells on the mooring lines. Further investigation of the platform motions and correlation to environmental conditions and relation to power performance and global thrust loads on the device will be presented.